The effect of the training with recessive hand on the hitting percentage of shots performed with the dominant hand for table tennis players - (:unkn) unknown (My University, 2013)
Bu araştırmada masa tenisçilerde tercih edilmeyen elle yapılan beceri çalışmalarının dominant el ile yapılan beceriler üzerindeki transfer etkisi araştırılmıştır. Araştırma, 20–25 yaş aralığındaki 20 masa tenisçi üzerinde yürütüldü ve antrenman programı 6 hafta boyunca haftada 5 gün devam etti. Her antrenman birimine ilave olarak resesif el ile 10 dakika antrenman yaptırıldı. Transfer durumu ikişer hafta aralıklarla test edildi ve analizlerde tekrarlı ölçümler varyans analizi (repeated measures ANOVA) kullanıldı. Bulgularda anlamlı değişimin 2. haftadan itibaren başladığı görüldü (p<.05). Sonuç olarak resesif elle antrenman yaptırıldığında dominant tarafa olumlu bir transfer etkisi olduğu gözlendi.

In this research, the transfer effect of the skill training with not-preferred hand for the table tennis players on the skills with the dominant hand was studied. The research was conducted on 20 table tennis players between the ages of 20-25, and the training program lasted for 6 weeks, 5 days a week for. In addition to every exercise, a 10- minute training with the recessive hand was carried out. The transferring condition was tested at two-week intervals, and the repeated measures variance analysis (repeated measures ANOVAs) was used in the analyses. It was seen that a significant change in the findings started as of the second week from the beginning(p <.05). Consequently, it was observed that the training with recessive hand has a positive transfer effect on the dominant side.
Masa tenisçilerde resesif el ile yapılan antrenmanın dominant el ile yapılan vuruşlarda isabet yüzdesi üzerine etkisi
Keywords: Spor Bilimleri; Eğitim, Eğitim Araştırmaları